2018
DOI: 10.1007/s10578-018-0830-8
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Mechanisms in Cognitive Behavioral Therapy for Childhood OCD: The Role of Dysfunctional Beliefs

Abstract: Reframing cognitions is assumed to play an important role in treatment for obsessive-compulsive disorder (OCD). However, there hardly is any empirical support for this assumption, especially for children. The aim of this study was to examine if changing dysfunctional beliefs is a mediating mechanism of cognitive behavioral therapy (CBT) for childhood OCD. Fifty-eight children (8-18 years) with OCD received CBT. Dysfunctional beliefs (OBQ-CV) and OCD severity (CY-BOCS) were measured pre-treatment, mid-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Indeed, improved set-shifting, inhibitory, visuospatial, verbal memory, and working memory abilities have been reported after CBT and cognitive training [58]. Moreover, dysfunctional beliefs decrease after CBT and cognitive therapy [56,59,60], although other authors found controversial results [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, improved set-shifting, inhibitory, visuospatial, verbal memory, and working memory abilities have been reported after CBT and cognitive training [58]. Moreover, dysfunctional beliefs decrease after CBT and cognitive therapy [56,59,60], although other authors found controversial results [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…approaching fear, increasing resistance), the youth may begin to understand the nonsensical or excessive nature of their symptoms and change their dysfunctional beliefs. 38 If so, it seems possible that poorer insight may still be expected to negatively impact the efficacy of placebo and medication (i.e., despite reductions in perceived distress, poorer insight does not lead to changes in behaviors or beliefs) which may partially explain the present study's differences from the findings that poorer insight predicted worse outcomes across treatments in the Pediatric OCD Treatment Study. 29 Regarding differences from adult findings, [23][24][25][26] pediatric OCD has been proposed as a developmental subtype that is distinct from adult OCD.…”
Section: Discussionmentioning
confidence: 67%
“…Several empirical studies have been conducted on CBT effects on OCD. In one study on 58 children and adolescents, measures taken at baseline, the midpoint and at the end of CBT suggested a decrease in dysfunctional beliefs and in the severity of OCD, with severity predicting the decrease in dysfunctional beliefs (Wolters et al, 2019). It is not clear whether the decreased symptoms occurred first followed by the decrease in dysfunctional beliefs or the reverse.…”
Section: Cognitive Behavior Therapy Effects On Ocdmentioning
confidence: 99%